Interactions of anthropogenic stress factors on marine phytoplankton - Häder, Donat-P.; Gao, Kunshan (Frontiers in Environmental Science, 2015)
Phytoplankton are the main primary producers in aquatic ecosystems. Their biomass production and CO2 sequestration equals that of all terrestrial plants taken together. Phytoplankton productivity is controlled by a number of environmental factors, many of which currently undergo substantial changes due to anthropogenic global climate change. Light availability is an absolute requirement for photosynthesis, but excessive visible and UV radiation impair productivity. Increasing temperatures enhance stratification, decrease the depth of the upper mixing layer exposing the cells to higher solar radiation, and reduce nutrient upward transport from deeper layers. At the same time, stratospheric ozone depletion exposes phytoplankton to higher solar UV-B radiation especially in polar and mid latitudes. Terrestrial runoff carrying sediments and dissolved organic matter into coastal waters leads to eutrophication while reducing UV penetration. All these environmental forcings are known to affect physiological and ecological processes of primary producers. Ocean acidification due to increased atmospheric CO2 concentrations changes the seawater chemistry; it reduces calcification in phytoplankton, macroalgae and many zoological taxa and enhances UV-induced damage. Ocean warming results in changing species composition and favors blooms of toxic prokaryotic and eukaryotic phytoplankton; it moderates UV-induced damage of the photosynthetic apparatus because of higher repair rates. Increasing pollution from crude oil spills, persistent organic pollutants, heavy metal as well as industrial and household wastewaters affect phytoplankton, which is augmented by solar UV radiation. In view of the fact that extensive analyses of the impacts of multiple stressors are scarce, here we review reported findings on the impacts of anthropogenic stressors on phytoplankton with an emphasis on their interactive effects and a prospect for future studies.